2016
DOI: 10.1007/s10803-016-2952-9
|View full text |Cite
|
Sign up to set email alerts
|

“It was like walking without knowing where I was going”: A Qualitative Study of Autism in a UK Somali Migrant Community

Abstract: Increasing recognition of autism in Somali migrant communities means that appropriate support services are needed. Attitudes to autism and barriers related to help-seeking in these communities are poorly understood. We aimed to assess what families affected by autism need, and how health, education and social care services can support them. In partnership with the local Somali community the research team conducted 15 in-depth interviews with parents affected by autism. Two themes are reported; ‘Perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(126 citation statements)
references
References 15 publications
(11 reference statements)
6
97
2
2
Order By: Relevance
“…Accordingly, providing speech and language interventions in both languages may help to alleviate the common risk of language attrition in the minority language (Bird et al 2016a). Considerations about cultural factors must also come to the fore when practitioners are advising multilingual parents, as certain communities may have concerns about the stigmatization of an autism diagnosis (Fox et al 2017;Ijalba 2016). Beauchamp and MacLeod (2017) and Lim et al (2018) call for more support for families wishing to raise their child on the autism spectrum bilingually.…”
Section: Recommendationsmentioning
confidence: 99%
“…Accordingly, providing speech and language interventions in both languages may help to alleviate the common risk of language attrition in the minority language (Bird et al 2016a). Considerations about cultural factors must also come to the fore when practitioners are advising multilingual parents, as certain communities may have concerns about the stigmatization of an autism diagnosis (Fox et al 2017;Ijalba 2016). Beauchamp and MacLeod (2017) and Lim et al (2018) call for more support for families wishing to raise their child on the autism spectrum bilingually.…”
Section: Recommendationsmentioning
confidence: 99%
“…Dillenburger et al [10] found that people from ethnic minorities were twelve times less likely to have heard of ASC, compared to those not from an ethnic minority. An example of cultural differences in attitude towards ASC within the UK can be found in the British-Somali community [21]. Qualitative research conducted with Somali migrants living in the UK has found that there is little acceptance of ASC as a condition among this population, and there is no word for 'autism' in the Somali language [21].…”
Section: Cultural Differencesmentioning
confidence: 99%
“…While an overview of the study findings has been published elsewhere (Fox et al 2016), stigma was identified as a key feature of the parenting experience which warranted further analysis. In this paper we explore the nature of stigma experienced by these parents and consider how they coped with or resisted such stigma, drawing on current stigma theory.…”
mentioning
confidence: 99%